Η ΠΟΛΙΤΙΚΗ ΚΑΙ ΔΙΠΛΩΜΑΤΙΚΗ ΠΑΡΟΥΣΙΑ ΤΟΥ ΚΩΝΣΤΑΝΤΙΝΟΥ ΖΩΓΡΑΦΟΥ ΣΤΟΝ ΑΓΩΝΑ (1821-1827) - ΟΙΚΟΝΟΜΟΠΟΥΛΟΥ - ΣΙΜΟΠΟΥΛΟΥ, ΜΑΡΙΕΤΤΑ (Μνήμων, 1972)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]-->Δεν παρατίθεται περίληψη<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->